2019
DOI: 10.1002/cbin.11185
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of TRPV6 channel activity by cholesterol depletion in Jurkat T cell line

Abstract: Transient receptor potential vanilloid 6 (TRPV6) channels are key players in calcium metabolism of healthy and cancerous cells. Nevertheless, the mechanisms controlling abundance of these channels in plasma membrane of the cells to regulate Ca2+ transport is still poorly understood. In this study, we provide the first evidence that TRPV6 calcium channels and Ca 2+ influx in Jurkat T cell line are modulated by cholesterol, a main lipid component of the plasma membrane. Using patch‐clamp technique, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The notion that TRPV6 functions as the primary epithelial Ca 2+ channel is well supported by findings made in mammalian cells over-expressing TRPV6 (Fecher-Trost et al, 2017) and by measuring endogenous TRPV6-mediated Ca 2+ influx in cultured Jurkat T cells and rat cauda epidermal principle cells (Gao et al, 2016; Kever et al, 2019). Fura-2 Ca 2+ imaging studies in cultured mammalian cells transfected with TRPV6 indicated that this channel is constitutively open (Vennekens et al, 2000).…”
Section: Discussionmentioning
confidence: 84%
“…The notion that TRPV6 functions as the primary epithelial Ca 2+ channel is well supported by findings made in mammalian cells over-expressing TRPV6 (Fecher-Trost et al, 2017) and by measuring endogenous TRPV6-mediated Ca 2+ influx in cultured Jurkat T cells and rat cauda epidermal principle cells (Gao et al, 2016; Kever et al, 2019). Fura-2 Ca 2+ imaging studies in cultured mammalian cells transfected with TRPV6 indicated that this channel is constitutively open (Vennekens et al, 2000).…”
Section: Discussionmentioning
confidence: 84%
“…Thus, it seems possible that those lipids bound under natural conditions has been shown to be, at least in parts, replaced in the excess of CHS [ 32 ]. Yet, consistent with possible binding sites of cholesterol within the channel, there are also functional data indicating that in Jurkat T cells, TRPV6 activity is sensitive to the depletion of this specific lipid [ 33 , 34 ]. Apart from cholesterol, different functional approaches point to phosphatidylinositol-4,5-bisphosphate (PIP 2 ) as an important regulator of TRPV6 and that specific channel characteristics are dependent on the levels of this lipid [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 85%
“…TRP vanilloid 5 and 6 (TRPV5 and TRPV6) channels are the most calcium selective channels in the TRP superfamily, with PCa/PNa >100 (compared with 0.3 for TRPM2). Recently, we have provided the first evidence that TRPV6 channel activity and TRPV6‐mediated Ca 2+ influx are dependent on lipid raft integrity in human leukemia Jurkat T‐cells (Kever et al, 2019). Using patch‐clamping and Ca 2+ imaging, we demonstrated that TRPV6‐mediated currents and Ca 2+ influx into Jurkat cells decreased following membrane cholesterol depleting with MβCD.…”
Section: Trp Channels In Lipid Microdomainsmentioning
confidence: 99%
“…It was found that TRPV6 association with lipid rafts and density of TRPV6 channels in the cell membrane declined significantly after disruption of rafts. Hence, lipid rafts regulated the activity of TRPV6 channels and Ca 2+ influx, thus affecting the location and density of channels in the Jurkat T‐cell plasma membrane (Kever et al, 2019).…”
Section: Trp Channels In Lipid Microdomainsmentioning
confidence: 99%